Murabahah Financing, Musyarakah, Mudharabah, Istishna and Ijarah Against Sharia Banking Profit Sharing - Bagus Ahmad Sudiro; Nurmala Ahmar; Ardiansyah (LPPM Universitas Terbuka, 2022)
In general, the principle of profit sharing in sharia banking can be done through murabahah, musyarakah, mudharabah, istishna dan ijarah contracts. The more profit sharing generated by Islamic banking, the better conditions of Islamic banking. The sample used and the data were obtained from 11 Islamic Banks in Indonesia for the period 2014-2018. Profit sharing is used as the dependent variable while murabahah, musyarakah, mudharabah, istishna, and ijarah financing are used as independent variables. The results of the research without resampling and with resampling show that murabahah, mudharabah, and istishna have a significant effect on profit sharing, and musyarakah and ijarah have no significant effect on profit sharing. Murabahah gives the most dominant influence on profit sharing.